Repeated use of buy-now-pay-later (BNPL) services: A reciprocal relationship of technological and behavioral attributes - Harimurti Wulandjani (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2026)
This study examines the reciprocal relationship between BNPL usage and consumer attitudes—specifically, perceived security, ease of use, pain of payment, and impulse-buying tendency—and how these attitudes influence subsequent BNPL usage. A time-lagged survey design was implemented with two waves of data collection (Time 1 and Time 2) over a six-month period, involving 357 Indonesian Gen Z consumers. Hypotheses were tested using structural equation modeling (SEM). BNPL usage at Time 1 is positively related to perceived security, ease of use, payment pain, and impulse-buying tendency. Perceived security, ease of use, and impulse-buying tendency, in turn, positively influence BNPL usage at Time 2, whereas payment pain negatively affects future usage. This research contributes to the literature by empirically validating a reciprocal model of BNPL usage that integrates technological and psychological determinants and highlighting the differential role of payment pain in a non-Western, Gen Z context.